Reasoning on urban open spaces’ relevance and their appropriation by the population: study carried out in Teresina City, Piauí State, Brazil - Lopes, Wilza Gomes Reis; Matos , Karenina Cardoso; Mesquita, Larissa de Fátima Ribeiro (National Journal of City Management, 2024)
Population distribution in Brazil is mostly urban and the number of people seeking urban centers keeps on growing. Therefore, the demand for areas designed to meet the basic needs of this human contingent also grows, like the case of spaces built for housing, commercial, industrial and service activities, as well as unbuilt open spaces accountable for articulating the spaces forming the urban fabric. Open spaces are highly accountable for shaping cities’ cultural identity, besides being important environmental improvement elements, in addition to being leisure places for the population. The current article provides an analysis of open spaces’ distribution in some city areas and the appropriation of an urban square. Southern Teresina City, Piauí State, Brazil, is the present object of study. A survey was carried out to quantify and map the existing squares in this site. Graphic records, photographic documentation and visual assessment were made to analyze the current situation of the existing equipment in the selected square. The space’s perceptual analysis was carried out and it focused on how the population uses this space. Neighborhoods Saci, Parque Piauí, Bela Vista and Promorar presented a larger number of squares due to the implementation of older and more consolidated housing complexes. Yet, Praça da Integração is widely used by the surrounding populations, although its equipment is not subjected to proper maintenance.